THE EFFECT OF PRICE AND QUALITY OF DEVILIA GLOW SKIN PRODUCTS ON CONSUMER BUYING INTEREST IN DEVILIA STORES IN TANJUNG BALAI KARIMUN - Rochmad Ponco Wasito; Dzirrusydi, Zalmi; Ana Mariana Kalbu Odjan; Raja Silvia Kencana Puri; Parizal, Parizal; Iyo King Siang (Indonesia Accounting Research Journal, 2024)
The purpose of this study is to determine the effect of price and product quality of Devilia Glow skin on consumers' purchase intention in Devilia stores in Tanjung Balai Karimun. This study uses quantitative methods. The population used is consumers of Devilia stores in Tanjung Balai Karimun. The sample used was 30 respondents using non-probability sampling technique (accidental), namely sampling by chance. Data processing is done using SPSS 16.0 software. Statistical data analysis using several tests including: (1) validity test and reliability test, (2) classical assumption test consisting of normality test, multicolonierity test, heteroscedasticity test, and multiple linear regression (3) hypothesis test consisting of T test, F test, and coefficient of determination test (R2). Based on the results of the hypothesis test that the price of Devilia glow skin has an effect on consumer buying interest in the Devilia store in Tanjung Balai Karimun. Can be seen from the results of t-test, namely the t-count price (X1) of 5.126> 2.051 t-table and sig 0.00 <0.05. then Ha is accepted and Ho is rejected. And the results of F-count for the independent variables (price and product quality) amounted to 20.317> 3.34 F-table and sig 0.00 <0.05. And then the results of the coefficient of determination (R2) test are 60.1%, indicating a strong degree of relationship.